A qualitative study of client experiences using stress inoculation coaching - McCormick, Iain (International Journal of Evidence Based Coaching and Mentoring)
Stress Inoculation Therapy (SIT) is an evidence-based method for mitigating adverse stress effects. Stress Inoculation Coaching (SIC) utilises the same approach as SIT but applies this to the non-clinical workplace population. SIC has four phases: awareness and knowledge building, skill development, application, followed by review and improvement. This study used a qualitative and interpretative phenomenological method to provide insights from ten clients who had experienced SIC. Clients regarded the SIC approach as useful and there can be cautious optimism about suitably trained, supervised and ethically adherent coaches using this approach. Further research is needed into the effectiveness of SIC.